Handbook of Depression - Friedman, Edward S.; Anderson, Ian M.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd., 2009)
The book provides an overview of the whole field of depressive disorders by two recognised experts. Written by well known authors, one European and one from USA this pocket-sized book covers the whole field including a practical guide of use in the clinic.
Classification, causes, and epidemiology -- Depression in different types of patients -- Diagnosis -- Principles of therapy -- Medications -- Other treatments -- Management of treatment nonresponse -- Continuation and maintenance treatment.
Keywords: Medicine; Psychiatry; Medicine & Public Health; Psychiatry; Electronic books